1999
DOI: 10.1161/01.atv.19.5.1340
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Postprandial Serum Paraoxonase Activity After a Meal Rich in Used Cooking Fat

Abstract: Abstract-Paraoxonase is an enzyme associated with HDL in human serum that hydrolyzes oxidized phospholipids and inhibits LDL oxidation, which is an important step in atherogenesis. In animals, addition of oxidized lipids to the circulation reduces paraoxonase activity, and diets rich in oxidized fat accelerate the development of atherosclerosis. The current randomized, crossover study was designed to compare the effect of a meal rich in oxidized lipids in the form of fat that had been used for deep-frying in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
4
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 57 publications
4
62
4
1
Order By: Relevance
“…The results of stepwise multiple regression analysis confirmed that the HDL-C alone and apo AI together with the PON1 polymorphisms were significant contributors to the variation in serum PON1 activity towards phenylacetate and diazoxon, respectively. Additionally, the effects of environmental factors such as diet and exercise on serum PON1 activity have also been reported by several studies (Tomas et al 2001(Tomas et al , 2002Sutherland et al 1999;).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The results of stepwise multiple regression analysis confirmed that the HDL-C alone and apo AI together with the PON1 polymorphisms were significant contributors to the variation in serum PON1 activity towards phenylacetate and diazoxon, respectively. Additionally, the effects of environmental factors such as diet and exercise on serum PON1 activity have also been reported by several studies (Tomas et al 2001(Tomas et al , 2002Sutherland et al 1999;).…”
Section: Discussionmentioning
confidence: 63%
“…This variation is partly due to PON1 gene polymorphisms although nutritional, pharmacological and environmental factors also affect PON1 levels (Sutherland et al 1999;Paragh et al 2000;Balogh et al 2001). The PON1 gene has two major coding region polymorphisms due to amino acid substitutions at position 55 (leucine to methionine; L/M) and at position 192 (glutamine to arginine; Q/R) (Adkin et al 1993;Humbert et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms are possible, including the following: (1) oxidized cholesterol accelerates the use of antioxidants such as vitamin E, thereby increasing the ability of other pro-oxidants to oxidize fatty acids or lipoproteins; (2) oxidized cholesterol, when present in lipoproteins, may alter the lipoprotein structure, so that fatty acids are more exposed and therefore more prone to oxidation; (3) oxidized cholesterol may inhibit the action of enzymes such as paraoxonase that protect lipoproteins from being oxidized. 41,42 Most importantly, our results demonstrate that oxidized cholesterol in the diet increases fatty streak lesions in aortas of both LDLR-and apo E-deficient mice (Figure 4). In LDLR-deficient mice fed diets that contained oxidized cholesterol, fatty streak lesions increased from 15.93% to 21.00% (32% increase).…”
Section: Staprans Et Al Atherogenicity Of Dietary Oxidized Cholesterolmentioning
confidence: 59%
“…PON is an antioxidant enzyme associated with HDL in human serum that hydrolyzes oxidized phospholipids and inhibits the LDL oxidation that is otherwise an important step in atherogenesis. In animals, the addition of oxidized lipids to the circulation reduces PON activity, and diets rich in oxidized fat accelerate the development of atherosclerosis [34]. Removal and inactivation of lipid peroxides which accumulate during LDL oxidation may be the central mechanism accounting for HDL antioxidative properties [35].…”
Section: Discussionmentioning
confidence: 99%